Becoming a resident : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Social Science at Massey University - White, Joan Margaret (Massey University, 1992)
In this thesis the meaning of relocation is examined for six elderly people in Northern Tasmania who voluntarily left their own homes and moved into two hostels for the frail aged. The research method of ethnography was used to guide the study. Periods of participant observation in the hostels and in-depth interviews with each of the six key participants, at approximately three monthly intervals over a nine month period following admission, were the main methods of data collection. Data was also obtained by interviewing other hostel residents, nursing staff associated with the relocation process, and significant others of the key participants. Data analysis occurred concurrently with data collection. Qualitative content analysis was used to inductively derive themes and sub-themes from the data. The themes and sub-themes were in turn validated with the key participants. Three major themes, "PREPARING FOR RELOCATION". "FITTING IN", and "LEADING THE LIFE I LIVED" emerged from the data. Preparing for relocation was a difficult time for the key participants. Decisions about where to relocate and what possessions to dispose of and what to keep had to be made. During this period, they were actively supported by professionals and significant others. Fitting into the hostel was a smooth process for five out of the six key participants. Some had been previously admitted on a short term basis and were familiar with staff and routine. Hostel staff were identified by the new residents as the most important group who helped in the adaptation phase. They facilitated residents self-care and encouraged them to pursue previous activities either within the hostel or in the community. Many features of the resident's new lifestyles were able to be integrated to provide continuity with their previous lifestyles as the key participants relocated in the same geographical area in which they had previously lived. Outside social contacts and recreations were maintained. One key participant exhibited features of poor adaptation to the hostel. She spent the day within the confines of her hostel room pursuing aspects of her previous lifestyle. The study demonstrated that for five out of six key participants the most stressful part of the relocation process occurred in the the preparation phase. Adaptation to the new environment and integrating aspects of old and new lifestyles were relatively smooth processes. Reasons for this smooth transition were concerned with the key participants making their own decisions regarding the choice of hostel and the timing of entry to the hostel. During these decision making processes, they were helped and supported by the professionals and significant others. Other reasons for the smooth transition period related to the key participants' knowledge of the hostel's physical surrounding, routine and staff. All key participants in one hostel had previously been admitted to the respite area adjoining the hostel. The key participants of this hostel also relocated from homes in the immediate neighbourhood thus they were able to easily maintain continuity with aspects of their previous lifestyles. The key participants in the other hostel did not have a choice of hostel accommodation. They belonged to a smaller rural community but were known by staff members and other residents prior to their admission. Staff members in the hostels also contributed to the smooth transition. They demonstrated positive attitudes towards the new residents adapting to the hostels and saw their roles as helping the elderly maintain their independence, thus providing an environment which helped the integration of old and new lifestyles.
Keywords: Older people -- Home care; Social aspects